Plan piloto para la producción de carne de llama y su comercialización en el mercado de Guayaquil para contribuir al mejoramiento de las condiciones de vida de los pobladores de la parroquia pungalá – provincia de Chimborazo - Vera Salazar, Lissette Patricia (2009)
Since ancients time humanity had know the good aptitudes of the llama as a working animal, later he discovered the benefits of its wool; hence its meat of this camel after some later years was just consumed by people who lived near it. Lately, the situation has reversed; there has been a process of revalue the mea that its extended to all the world. These animals had the particulate of development feeding them with low quality grass and low level of digestible where other animals where express severe problems to survive. Another important date it is its longevity; in that sense, as a media, they can survive as long as 14 to 20 years. In our country, the race of these animals had been increasing gradually in different zones. In these aspect, its important to mention that its production doesn’t required specific structure, neither to required to complicated systems, in general lines it can be race in cow installations, chasing the sanity and services according to its anatomy. In a health aspect, it’s a very healthy animal, it can had some illness origin in other camels that can coexist in the exploitation, such as flee, but its not necessary to be vacuum for the aftosa. The meat of this animal is not that different for the cow meat, it is very white and it doesn’t have too many levels of cholesterol, reason why is very recommend to its consumption by nutritionist Considering this situation, we propose this next investigation to increase the distribution of the llama’s meat and therefore contributed to the development of the region.